RUMAH SEBAGAI PUSAT PENDIDIKAN DAN RUANG IBADAH HOME AS A CENTER OF EDUCATION AND WORSHIP - Diana, Resiska Eka; Hura, Rosnila (Sekolah Tinggi Teologi Injili Abdi Allah, 2022)
Abstract: The pandemic period has changed everything in terms of economic, social and even what we can see most prominently, namely education and worship. At the beginning of the spread of the corona virus in December 2019 the government issued a decision that activities or activities were carried out at home until now. This of course hinders every community activity where people who work in companies, factories, teachers, and other workers are carried out at home, besides that many people even lose their jobs. but in this case the important focus is education and worship is done at home, so that the house becomes the center. Of course this will be a problem and a big change for children, parents and also for every congregation. Because of that, the obstacles it faces will appear, such as the media that is less accommodating, time and also the understanding of people's thoughts. For this reason, the purpose of writing this article is to provide an understanding to every reader, namely the importance of the house as a center of education and worship during the pandemic to increase knowledge and maintain the faith that is held. The research method used by the author is a study of literature or literature. Key Words: House, Education Center, Worship Room Abstrak: Masa pandemi membuat segala sesuatu berubah dari segi ekonomi, sosial dan bahkan dapat di lihat hal yang paling menonjol yaitu pendidikan dan juga peribadahan. Pada awal adanya penyebaran virus corona pada Desember 2019 pemerintah mengeluarkan keputusan bahwa aktivitas atau kegiatan dilakukan di rumah hingga saat ini. Hal ini tentunya menghambat setiap kegiatan masyarakat yang dimana orang yang bekerja di perusahan, pabrik, guru, dan pekerja lainnya dilakukan di rumah, selain itu bahkan masyarakat banyak yang kehilangan pekerjaan. akan tetapi dalam hal ini yang menjadi sorotan penting yaitu pendidikan dan peribadahan di lakukan di rumah, sehingga rumah menjadi pusat. Tentunya ini akan menjadi permasalahan dan perubahan yang besar bagi anak, orang tua dan juga bagi setiap jemaat. Karena itu akan muncul penghambat-penghambat yang dihadapinya seperti media yang kurang mewadahi, waktu dan juga pemahaman pemikiran dari masyarakat. Untuk itu tujuan penulisan artikel ini yaitu untuk memberikan pemahaman kepada setiap pembaca yaitu pentingnya rumah sebagai pusat pendidikan dan peribadahan dimasa pandemi untuk meningkatkatkan pengetahuan dan mempertahankan iman yang di pegang. Metode penelitian yang digunakan oleh penulis adalah study pustaka atau literatur. Kata Kunci: Rumah, Pusat Pendidikan, Ruang Ibadah